Antimicrobial effectiveness in vitro of the Papacarie® in samples from the decayed tissue in primary school students - Alvarado Villanueva, Verónica (2010)
With the purpose of determinate the antimicrobial activity of the Papacarie® in the time indicated by the manufacturer (30seconds), samples were taken from caused to decay weave of temporary pieces without commitment to pulpar of five children of the school Andrés Rázuri, to analyze in vitro the sample with the product. Taking into account that the product requires to be in contact with the sample a short time, discs with the Papacarie® became absorbed and faced this by 15, 30 and 60 seconds, the discs were retired and the sample in Agar Mitis Salivarius Bacitracina was seeded. The obtained counts of the controls made to 24, 48 and 72 hours, were analyzed with T Student statistical analysis. The results demonstrated that with the used methodology a significant difference between the antimicrobial activity and the indicated application times does not exist.